Karakterisasi Bakteri Bacillus thuringiensis asal Hutan Lindung Kampus Uncen Jayapura, serta Deteksi Toksisitasnya terhadap Larva Nyamuk Anopheles - Daniel Lantang; Dirk Y.P. Runtuboi (Jurnal Biologi Papua, 2012)
Study of isolate characterization of Bacillus thuringiensis Berliner collected from soil was done at UNCEN Campus. The aims of the study were to explore the local isolate of B. thuringiensis and to study the toxicity of the isolates on larvae of Anopheles as a vector of malaria and filariasis deseases in Papua. Data was analized by Hadioetomo & Rusmana method (1977). The results showed that 383 colonies are relatively closed to B. thuringiensis whereas 290 of them are indicated as local isolates of B. thuringiensis. Based on toxicity detection on larvae of Anopheles found that 19 isolates have toxicities levels 50% or more. Among the 19 isolates 3 of them has 80%, 85% and 90% toxicity levels separately.Key words: Characterization, local isolate, B. thuringiensis, toxicity, and soil.